PERAN PUSTAKAWAN TERKINI: SEBUAH TINJAUAN LITERATUR - Purnama, Radhitya (Perpustakaan Nasional RI, 2024)
This research aims to identify the role of librarians in the social framework of the current information era. To achieve this aim, the research conducted a literature review of the Scopus database from 2014 to 2024. A total of 137 articles that met the inclusion criteria were analyzed to explore the role of librarians in various library contexts. Given the limited resources, the analysis focused only on the titles and abstracts of the articles. The results of the analysis show that academic libraries are the type of library most often discussed regarding the role of librarians today. The four main themes identified are: (1) role in digital information and resource management which includes the role of data management, providing information based on specific subjects, acquisition and development of digital collections, planning technology implementation, management of open scientific series, (2) involvement and community education, which consists of educational roles, especially in aspects of information literacy and reaching the wider community to improve their quality of life, (3) library services which describe the role of librarians in online reference services, part of the research cycle, and adaptation of the latest technology to improve services, as well as (4) preservation, which includes the digitization of local wisdom by paying attention to cultural protocols. Overall, the role of librarians can effectively support the culture of research and innovation in institutions. Librarians also need to continually adapt to new technology and develop relevant skills.